Jawabanmu

Jawaban paling cerdas!
2014-07-03T00:09:26+07:00
x=1, y= -1 dan z= 2
ax+by-3z = -3    ⇔    a - b - 6 = -3      ⇔    a - b = 3  .........................(1)
-2x-by+cz = -1   ⇔   -2 + b + 2c = -1  ⇔    b + 2c = 1 ........................(2)
ax+3y-cz = -3
    ⇔    a - 3 - 2c = - 3   ⇔    a - 2c = 0  ........................(3)
dari persamaan 2 dan 3 didapat
b + 2c = 1
a - 2c = 0 +
a + b = 1 ..........................(4)
dari persamaan 1 dan 4 didapat
a - b = 3                                    a + b = 1 ⇔ 2 + b = 1 maka b = - 1
a + b = 1 +                                b + 2c = 1 ⇔ - 1 + 2c = 1 ⇔ 2c = 2 maka c = 1
2a = 4 maka a = 2
Jadi, nilai a + b + c = 2 - 1 + 1 = 2
1 5 1